2011
DOI: 10.1039/c1cc15663b
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular assembly and thermo-responsive vesicle-to-micelle transition from an amphiphilic random copolymer

Abstract: Vesicular assembly from a thermo-responsive amphiphilic random copolymer is reported. Vesicle-to-micelle transition above a critical morphology transition temperature (CMTT) resulted in selective triggered release of encapsulated hydrophilic guests over hydrophobic ones. The aggregation pattern of a control polymer indicated a defined role of the methacrylamide groups in the polymer backbone for such unprecedented self-assembly from a simple polymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 45 publications
1
70
0
Order By: Relevance
“…From a practical point of view, RCPs are much easier to synthesize than BCPs, which require multistep living polymerization procedures. Easier synthesis and morphological versatility make the RCPs great candidates for many applications, from drug encapsulation to optical materials and microelectronics …”
Section: Introductionmentioning
confidence: 99%
“…From a practical point of view, RCPs are much easier to synthesize than BCPs, which require multistep living polymerization procedures. Easier synthesis and morphological versatility make the RCPs great candidates for many applications, from drug encapsulation to optical materials and microelectronics …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the vesicular assembly is suitable for delivery vehicles owing to the structure of as-biological membrane. [31] …”
Section: The Influence Of the External Condition On Selfassembly Morpmentioning
confidence: 99%
“…3 Over the past few decades, numerous stimuli-sensitive micelles that respond to various stimuli, 4 such as pH, 5,6 temperature, 7,8 light, 9 redox species, 10 enzymes, 11 and ultrasound, 12,13 have been reported. In recent years, multisensitive micelles have become increasingly prevalent because they mimic the behavior of natural responsive materials and have high efficiency.…”
mentioning
confidence: 99%